Factors Influencing Nursing Rounds in the Inpatient Ward Otanaha Regional Hospital, Gorontalo City - Abdul Rahman Yusuf; Sabirin B. Syukur; Euis H. Hidayat; Rini Asnawati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
The nursing round will deliver media for nurses to discuss more deeply health problems and patient needs and is a learning process for nurses using the hope of improving cognitive, effective, and psychomotor skills. The sensitivity and critical thinking of nurses will grow and be trained through a transfer of knowledge and the application of theoretical concepts into nursing practice.Objective : This study aims to find out the factors that affect the nursing round in the inpatient room of Otanaha Hospital, Gorontalo City.Methods : This study used an alanalytic descriptive design with a cross-sectionall approach. Alanalytic research is research that aims to clarify the relationship between one variable and another. Cross sectionall research is a study to study the dynamics between factors that affect the nursing round in the inpatient room of Otanaha Hospital, Gorontalo city. The results of the statistical test using Spearmen's rho showed that there was a very significant relationship (p 0.030) between implementation and subjective norms in the nursing round in the Inpatient Room of Bajawa Hospital, East Nusa Tenggara. The results of the static test showed a sufficient correlation (r0.219) which means that the relationship between the variables is balanced with a balanced value of 1.Results : From the results of the statistical test using the wilcoxon test, the influence of knowledge on the implementation of the nursing round in the Inpatient Room of Otanaha Hospital, Gorontalo City was obtained with a p value of 0.0002. From the results of the statistical test using the wilcoxon test, it was found that the influence of attitude on the implementation of the nursing round in the Inpatient Room of Otanaha Hospital, Gorontalo City with a p vallue value of 0.003. The implementation of the nursing round will go well with good knowledge, a positive attitude, good subjective norms, and good intentions from the nurse to carry out the nursing round. Therefore, training on nursing rounds and the implementation of nursing rounds regularly and continuously are needed. It is hoped that with these improvements, the implementation of nursing rounds can be more optimal and contribute to improving the quality of patient care